Pengaruh Permainan Berburu Harta Karun Terhadap Kemampuan Motorik Kasar Anak Usia 5-6 Tahun Di TK Bunda Karya Kabupaten Bengkalis - Farradina Prima Putri; Nurlita Nurlita; Defni Satria (Innovative: Journal Of Social Science Research, 2023)
Treasure hunting games affect the gross motor skills of children aged 5-6 years.This study aims to determine the effect of treasure hunting games on gross motor skills of children aged 5-6 years at Bunda Karya Kindergarten, Bengkalis Regency. The type of research used is experimental research with quantitative methods. The sample used was 25 people. The research used in this research is experimental research that influences the independent variables on the dependent variable. The research method used was pre-experiment with the Pretest-Posttest Only Control Group Design. The sampling technique used in this research is saturated sample. Data collection techniques used through objective tests. This research hypothesis is that there is an influence of treasure hunting games on gross motor skills of children aged 5-6 years at Bunda Karya Kindergarten, Bengkalis Regency. The effect given by treasure hunting games on the gross motor skills of children aged 5-6 years at Bunda Karya Kindergarten, Bengkalis Regency is 66.32%.